Physical Condition of Dig Well and Incidence of Diarrhea in Infants at The Working Area of Kabila Community Health Center - Bun Yamin M. Badjuka; Tumartony Thaib Hiola (Health Notions, 2019)
Dig well is one of the clean water supply sources for the society in the countryside, and urban areas. Dig well provides water originating from the soil layer that is relatively close with ground level, therefore susceptible to contamination through seepage originating from human waste, animals, or for domestic household needs. Dig well as clean water source must be supported by construction conditions, location conditions to build a dig well, this thing is needed so that the quality of dig well’s water is safe according to the rules set. The research purpose is to know the physical condition of dig well with incidence of diarrhea in infants at the working area of Kabila Community Health Centre Bone Bolango District. This research used quantitative method, the research instrument uses observation sheet and questionairres to measure the physical condition of dig well. The result show that there was a significant effect between dig well lip height variable, wall of the dig well, septic tank distance with dig well by the incidence of diarrhea in infants. For the variable of dig well floor and closing condition of dig well obtains the result that there was no influence with the incidence of diarrhea in infants. Keywords: Physical condition, Dig well, Diarrhea